Gradient identification method of the model parameters for electrohydraulic servo drive of FESTO learning system. Issue 1 (November 2020) - Kulakov, B; Kulakov, D; Qi, Long
Abstract: Gradient identification method of the model parameters for electrohydraulic servo drive is considered. The method is adapted to be implemented by an experimental complex consists from FESTO hydraulic learning system and Matlab/Simulink. The implementation of the considered identification algorithm in the Matlab/Simulink package is shown.